Analisis Permasalahan Guru Mata Pelajaran Geografi Kelas X dalam Menerapkan Kurikulum Merdeka Belajar di SMA Negeri 1 Kayan Hilir Kabupaten Sintang - Agus Suwarno; Yuni Kristina (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Analysis of the Problems of Grade X Geography Subject Teachers in the Implementation of the Independent Learning Curriculum at SMA Negeri 1 Kayan Hilir, Sintang Regency, is a study that aims to reveal the problems of the case study. The research informants include the principal, vice principal for curriculum, and grade X geography teachers. The data collected consists of primary and secondary data, using direct observation techniques, interviews, and documentation. Data collection tools are in the form of observation guidelines, interview guidelines, and documentation. Research Results Problems.